PENGARUH MANAJEMEN DEWAN KEMAKMURAN MASJID (DKM) TERHADAP KESADARAN SHALAT BERJAMAAH DI DESA SETIA BUDI - Ulfah Dina Maryati; Yasafik Yasafik; Aprizal Aprizal (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2023)
The mosque prosperity council has an important role as a driving force for all mosque activities. Their function is needed to create mosque programs, one of which is congregational prayer. The aim of this research is to look from a scientific point of view at the relationship between mosque prosperity council management and the awareness of congregational prayer among residents around the mosque. This type of research was quantitative research with a correlation method, where data collection techniques used questionnaires and documentation. The information obtained and analyzed using the product moment formula. The result of this research are: 1) management of the mosque prosperity council is in the medium category; 2) the level of awareness of congregational prayer is in the medium category; and 3) there is a relationship between the management of the mosque prosperity council and awareness of congregational prayer. The relationship between the independent variable and the dependent variable is in a positive relationship, it means that if the DKM management can improve its performance, the awareness of congregational prayer can improve among local residents. So that the congregational prayer program can increase in quantity aspect.